KEBIJAKAN PEMERINTAH DAERAH DALAM PENYELENGGARAAN PELAYANAN EKTP - HILAPOK, LEONAR SON; RORONG, ARIE; DENGO, SALMIN (Sam Ratulangi University, 2018)
Abstract: It has been understood that a policy is created because there is a goal to be achieved. Without goals, thereis no need for policy so the goal becomes the first element of a policy. Good policy has a good purpose. Excellentservice to the Society becomes and eminent issue in the implementation of its duties and responsibilities within thebureaucracy of increasing the level of knowledge of Society. Despite the influence of Globalization, the old patternsof government administration are no longer compatible with the changing social life of the Society, whichencourages researchers to examine, Local Government Policy in the implementation of e-ID card service inPyramid District.The method used in this research is descriptive method of analysis, with data collection through questionnairesurvey and interview with the information giver that is needed in this research is Society in Pyramid District whichtake care of e-KTP, KK and Birth Certificate and data analysed descriptively descriptive analysis with Descriptivestatistics.The results of the research show that: (1) The application of the principle of Transparency and Accountabilityattitude in the implementation of Public service in Pyramid District Not yet optimal / Still in very low level not inaccordance with the expectation of Society in four. (2) The productivity of District Government in policymaking isnot appropriate on the target according to the standard of Public Service and even the Vision and Mission in theDistrict. (3) The quality of government work Pyramid district in the implementation of duties and responsibilitiesis not too optimal in the low category is not yet able to match the expectations and desires Society. Researcherscleared the conclusion that the policy in the service delivery as a servant of the state in Pyramid District Office hasnot been implemented as expected by Society. For that, researchers suggest to improve the transparency andaccountability of public services more optimal public service productivity.Keywords: Policy is a, A deep analysis of the alternatives that leads to, Public Interest in accordance with. LegalLegality of RI.PENDAHULUANKebijakan publik merupakan salah satu dimensipokok dalam ilmu dan praktik AdministrasiPublik. Sebagai salah satu unsur penting dalamAdministrasi Publik, Kebijakan publikdianalogikan sama dengan fungsi otak pada tubuhmanusia, karena instrument ini segala aktifitaskehidupan bernegara, dan bermasyarakat mulaidilakukan oleh birokrasi, plus pihak swasta danmasyakat. Tantangan dalam menghadapilingkungan global mengubah kita dalam carapandang sebagai abdi negara (apparat negara),untuk mampu mengakomodasikan perubahansecara demokratis dan konstitusional dengantetap menjaga stabilitas dan integrasi nasiona